IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH WORD WALL TECHNIQUE - Rivalen A. Maindoka; Sanerita T. Olii; Rinny Rorimpandey (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
The aim of this research is to see whether the use of the Word Wall Technique can improve students’ vocabulary mastery or not. This research is conducted in the seventh grade of SMP BEREA Tondano, class VII is chosen as the subject of the study and this class consists of fifteen (15) students. This research uses the pre-experimental design with one group pre-test and post-test. The instrument for data collection is a multiple-choice test. In this research showed that the mean score of the pre-test is 49,6 and the post-test is 82. This means that the result of post-test is higher than pre-test. In other words, this result may lead to conclusion that using Word Wall Technique is effective to improve students’ vocabulary mastery at the seventh grade of SMP BEREA Tondano. This shows that English teacher can use Word Wall Technique to improve students’ vocabulary mastery.